Write the equation y2 + 6y - 12x - 39 = 0 in standard form.
O ( + 9)2 = 12(x + 4)
O U + 3)2 = 12(x + 4)
O ( + 3)2 = 12x + 39
O ( + 9)2 = 12x + 39

Respuesta :

Answer:

B

Step-by-step explanation:

I got it right on EDG21

The standard form of the given equation y^2 + 6y - 12x - 39 = 0 would be equal to (y + 3)^2 = 12(x + 4). Hence, the correct option is B.

What is a system of equations?

A system of equations is two or more equations that can be solved to get a unique solution. the power of the equation must be in one degree.

The given equation is

y^2 + 6y - 12x - 39 = 0

Solving;

y^2 + 6y - 12x - 39 = 0

y^2 + 6y = 12x + 39

From the RHS;

12x + 39

12x + 48 - 9

= 12(x + 4) - 9

From the LHS, take out y as a common;

y^2 + 6y + 9 = (y + 3)^2

Therefore, the  standard form of the given equation y^2 + 6y - 12x - 39 = 0 would be equal to (y + 3)^2 = 12(x + 4).

Hence, the correct option is B.

Learn more about equations here;

https://brainly.com/question/10413253

#SPJ2

ACCESS MORE